Novels, Histories, Novel Nations Historical Fiction and Cultural Memory in Finland and Estonia - Kaljundi, Linda; Laanes, Eneken; Pikkanen, Ilona (Studia Fennica Historica, 2015)
"This volume addresses the prominent, and in many ways highly similar, role that historical fiction has played in the formation of the two neighbouring 'young nations', Finland and Estonia. It gives a multi-sided overview of the function of the historical novel during different periods of Finnish and Estonian history from the 1800s until the present day, and it provides detailed close-readings of selected authors and literary trends in their social, political and cultural contexts. This book addresses nineteenth-century 'fictional foundations', historical fiction of the new nation states in the interwar period as well as post-Second World War Soviet Estonian novels and modern historiographic metafiction. The overall focus is on traditions of writing rather than on isolated highpoints, on chains of transnational influences and on narrative elements that recur both synchronically and diachronically. The volume shows historical fiction prefigured many narratives, tropes, heroes and events that academic history writing later adopted. The comparison of the two literary traditions also opens up a much broader view of how historical novels narrate the nation. While existing explorations of historical fiction have mostly been written from the perspective of the old and great nations, this book shows that the traditions of the young nations 'without history' often challenge many mainstream views on the genre."